Towards an Efficient Protocol for the Determination of Triterpenic Acids in Olive Fruit: A Comparative Study of Drying and Extraction Methods - Goulas, Vlasios; Manganaris, George A. (My University, 2012)
Introduction Triterpenic acids, such as maslinic acid and oleanolic acid, are commonly found in olive fruits and have been associated with many health benefits. The drying and extraction methods, as well as the solvents used, are critical factors in the determination of their concentration in plant tissues. Thus, there is an emerging need for standardisation of an efficient extraction protocol that determines triterpenic acid content in olive fruits. Objective To evaluate common extraction methods of triterpenic acids from olive fruits and to determine the effect of the drying method on their content in order to propose an optimum protocol for their quantification. Methodology The efficacy of different drying and extraction methods was evaluated through the quantification of maslinic acid and oleanolic acid contents using the reversed-phase HPLC technique. Results Data showed that ultrasonic assisted extraction with ethanol or a mixture of ethanol:methanol (1:1, v/v) resulted in the recovery of significantly higher amounts of triterpenic acids than other methods used. The drying method also affected the estimated triterpenic acid content; frozen or lyophilised olive fruit material gave higher yields of triterpenic acids compared with air-dried material at both 35°C and 105°C. Conclusion This study provides a rapid and low-cost extraction method, i.e. ultrasonic assisted extraction with an eco-friendly solvent such as ethanol, from frozen or lyophilised olive fruit for the accurate determination of the triterpenic acid content in olive fruit
Keywords: Freeze-drying; Oleanolic acid; Chemical structure; Cost; Hydration; Lantana camara; Olive; Solubilization; Solvent extraction; Spray drying